Outbreak of Monkeypox Virus Disease: An Update on Epidemiology, Pathophysiology and Available Treatment Options - Kumar, Akash; Angaria, Neeti; Singh, Gurvinder; Kumar, Rajesh (Infectious Disorders - Drug Targets, 2023)
The monkeypox virus is a zoonotic illness with a tropical distribution in Africa, and around the world. The disease is spread through contact with infected animals or humans, and can also be spread from person to person through close contact with respiratory or bodily fluids. Fever, swollen lymph nodes, blisters, and crusted rashes characterize the disease. The incubation period is five to twenty-one days. It is difficult to distinguish the rash caused by infection from varicella and smallpox. Laboratory investigations are essential aspects of illness diagnosis and surveillance, and novel tests are required for more accurate and faster diagnosis. Antiviral drugs are being used to treat monkeypox. Scarring as well as other comorbidities, are prevalent in survivors, with the case mortality rate varying from 1 to 11%. The virus was found in monkeys at a Danish research facility in 1958, from which the term ‘monkeypox’ is derived. The primary human case was found in a child in the Democratic Republic of the Congo (DRC) in 1970. The World Health Organisation (WHO) has recently declared monkeypox a public health emergency of international concern. This manuscript attempts to review the various aspects of monkeypox disease and its allopathic as well as alternative treatment options available and serves as a valuable resource for healthcare professionals, researchers, and the general public.
Keywords: zoonotic viral disease